2021
DOI: 10.1093/toxsci/kfaa192
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Methylmercury Metabolism and Elimination in Humans: Physiological Pharmacokinetic Modeling Highlights the Role of Gut Biotransformation, Skeletal Muscle, and Hair

Abstract: The biological half-life (t1/2) of methylmercury (MeHg) shows considerable individual variability (t1/2 < 30 to > 120 days), highlighting the importance of mechanisms controlling MeHg metabolism and elimination. Building on a prior physiologically based pharmacokinetic (PBPK) model, we elucidate parameters that have the greatest influence on variability of MeHg t1/2 in the human body. Employing a dataset of parameters for mean organ volumes and blood flow rates appropriate for man and woman (25–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“… 50 For MeHg, Rand’s group developed computational pharmacokinetic models that predicted a shorter MeHg half-life in women than men and a shorter half-life in children than adults. 49 The models also identified skeletal muscle mass as a potential storage compartment that can delay the fecal excretion of MeHg. 49 Because both iAs and MeHg are transported across the gut epithelium into the bloodstream and from the liver into the blood or bile, any host or microbial effects on transport efficiency, gut barrier function, and tissue absorption rates also modulate metabolism and body burden.…”
Section: Variations In Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“… 50 For MeHg, Rand’s group developed computational pharmacokinetic models that predicted a shorter MeHg half-life in women than men and a shorter half-life in children than adults. 49 The models also identified skeletal muscle mass as a potential storage compartment that can delay the fecal excretion of MeHg. 49 Because both iAs and MeHg are transported across the gut epithelium into the bloodstream and from the liver into the blood or bile, any host or microbial effects on transport efficiency, gut barrier function, and tissue absorption rates also modulate metabolism and body burden.…”
Section: Variations In Toxicitymentioning
confidence: 99%
“… 49 The models also identified skeletal muscle mass as a potential storage compartment that can delay the fecal excretion of MeHg. 49 Because both iAs and MeHg are transported across the gut epithelium into the bloodstream and from the liver into the blood or bile, any host or microbial effects on transport efficiency, gut barrier function, and tissue absorption rates also modulate metabolism and body burden. 54 , 68 , 69 , 70 , 71 …”
Section: Variations In Toxicitymentioning
confidence: 99%
“…On the other hand, it has been reported that MeHg can affect the gut microbiota of various organisms [18] , such as pregnant women, walruses and zebra sh [19][20][21] . The destruction of gut microbiota accelerated the accumulation of mercury in organs [22][23][24] . For example, it was found that antibiotics treatment led to increased accumulation of MeHg in sh [25] .…”
Section: Introductionmentioning
confidence: 99%